2012
DOI: 10.1038/eye.2012.190
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms compensating for visual field restriction in adolescents with damage to the retro-geniculate visual system

Abstract: Background To describe visual field (VF) outcome in three adolescents with damage to the optic radiation and to focus on mechanisms that may compensate the practical functional limitations of VF defects. Design Descriptive, prospective multi-case study in a hospital setting. Participants Three teenagers with cerebral visual dysfunction because of damage to the retro-geniculate visual pathways. Methods Best-corrected visual acuity and eye alignment were assessed. Visual field function was tested with Goldmann p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 25 publications
2
5
1
Order By: Relevance
“…This phenomenon was first reported by Herzau et al., who described two adult patients with HH and XT, both existing from early childhood, that led to functional enlargement of the binocular visual field, an observation later confirmed by Saleh et al . and Jacobson et al . In our study, the postoperative shift of ocular alignment to contralateral XT advocates a compensatory origin.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…This phenomenon was first reported by Herzau et al., who described two adult patients with HH and XT, both existing from early childhood, that led to functional enlargement of the binocular visual field, an observation later confirmed by Saleh et al . and Jacobson et al . In our study, the postoperative shift of ocular alignment to contralateral XT advocates a compensatory origin.…”
Section: Discussionsupporting
confidence: 87%
“…We speculate that these children somehow prefer the expansion of the functional visual field by means of contralateral XT above normal ocular alignment. In addition, several authors have suggested that the expected double vision might be avoided when this functional visual field enlargement by XT is accompanied by an anomalous retinal correspondence, resulting in continuous XT, or by using scanning movements into the blind field, observed as intermittent XT . Both continuous and intermittent were observed in our hemispherectomized children.…”
Section: Discussionmentioning
confidence: 56%
See 2 more Smart Citations
“…Consequently, they had no (or only mild) diffi culties in everyday life activities, at least no more 'diffi culties' than children of the same age may also have. Numbers in brackets refer to bilateral visual fi eld impairment N number of subjects, UNI, BIL uni-and bilateral visual fi eld loss It is possible that in some cases, the development of divergent strabismus develops and becomes compensatory for the hemianopia, and care has to be taken when considering cosmetic strabismus surgery (Jacobson et al 2012 ). In the context of neurological and neuroradiological examinations of an 11-year-old girl with suspected epilepsy, a small cystic lesion was detected in the left occipital lobe.…”
Section: Visual Fieldmentioning
confidence: 99%